Tindak pidana Cyber Pornografy dalam perspektif Undang-Undang Nomor 44 Tahun 2008 tentang Pornografi dan Undang-Undang Nomor 19 Tahun 2016 tentang Informasi dan transaksi elektronik - Khairiah, Umi; Maswita, Maswita; Warsiman, Warsiman (Fakultas Hukum Universitas Al Azhar Medan, 2024)
One of the negative impacts of technological progress is the spread of pornographic information, which has become a serious concern for all parties, including the government, law enforcement officials, practitioners and academics, as well as society in general. Pornography crimes most often occur in cyberspace by displaying photos, videos, stories and moving images. For example, the case involving a female YouTuber from Sidoarjo who was convicted of committing the crime of pornography in the Wates District Court Decision Number 23/Pid.B/2022/PN.Wat. Regulations regarding cyber pornography in the provisions of Law no. 11 of 2008 concerning Information and Electronic Transactions and Law no. 44 of 2008 concerning pornography has complex legal regulations in Indonesia, but for cyber pornography there is no comprehensive regulation. The type of criminal act of pornography via electronic media which is regulated in Article 27 paragraph (1) of the ITE Law is a formal offense because the article only describes prohibited acts, such as every person intentionally and without the right to distribute and/or transmit and/or make it accessible. electronic information and/or electronic documents that contain content that violates decency. Meanwhile, the elements of the consequences of prohibited acts are not described in the article because the consequences of cyberporn crimes are personal offenses, meaning that the consequences cannot be measured objectively. Apart from that, Article 27 paragraph (1) of the ITE Law aims to protect individual rights or concerns a person's right to privacy, therefore this article is regulated as a formal offense, not a material offense. Meanwhile, the prohibition on the dissemination of pornographic content, including via the internet, in the Pornography Law is regulated in Article 4 paragraph (1). The judge's considerations in imposing a crime in decision case number: 23/Pid.B/2022/PN.Wat have taken into account both juridical and non-juridical facts. In choosing the charges, the judge also considered which charges were deemed most appropriate, namely the first charge, namely violating the provisions of Article 29 in conjunction with Article 4 paragraph (1) of Law no. 44 of 2008 concerning Pornography in conjunction with Article 64 paragraph (1) of the Criminal Code. The judge's application of law in the Wates District Court decision Number: 23/Pid.B/2022/PN.Wat is in accordance with the provisions of statutory regulations